Nazi crimes and their punishment, 1943-1950 : a short history with documents - Bryant, Michael S. 1962- (Passages: Key moments in History, 2020)
Chronology of Nazi crimes and trials, 1919-1957 -- Historical essay -- Brief historiographical essay -- Documents. Enabling laws : the legal foundations of postwar courts trying Nazi crimes -- The Nuremburg war crimes trials : selected trial documents -- Trials by army courts : the Belsen and Dachau trials -- Trials by Polish courts -- Trials by Soviet courts : the Kharkov trial, December 15-18, 1943 -- Trials by German courts.